Iatrogenic Type A Aortic Dissection: Challenges and Frontiers—Contemporary Single Center Data and Clinical Perspective - von Aspern, Konstantin; Leontyev, Sergey; Etz, Christian D.; Haunschild, Josephina; Misfeld, Martin; Borger, Michael A. (AORTA, 2022)
Iatrogenic aortic dissection (IAD) is a rare but devastating complication in cardiac surgery and related procedures. Due to its rarity, published data on emergency surgery following IAD are limited. Herein, we discuss IAD occurring intra- and postoperatively, including those occurring during transcatheter aortic valve replacement and cardiac catheterization, and present benchmark data from our consecutive, single-center experience. We demonstrate changes in patient characteristics, surgical approaches, and outcomes over a 23-year period.
Keywords: iatrogenic aortic dissection; Type A; complications associated with cardiac surgery